Absence of K cells in human gut mucosa. Issue 4 (April 1978) - Clancy, R; Pucci, A
Abstract : Lymphocytes have been isolated from human rectal biopsies in numbers sufficient for microassay procedures. No antibody-dependent cell-mediated cytotoxic (ADCC) activity could be detected in normal or inflamed human gut mucosa, using two assay systems which detect predominantly K cell activity. The tissue localisation and circulation characteristics of K cells require definition before establishing their role as an efferent immunological mechanism.